Marshall cavendish maths pupil's book 5 - Po, Huat Seng; Soon, Spario (Marshall Cavendish Education Singapore, 2017)
Mathematics. 5, Pupil's Book is designed to support young learners in Grade 5 with foundational math concepts. The book introduces key topics such as number operations, fractions, geometry, measurement, and problem-solving. It presents exercises and activities aimed at enhancing logical reasoning, critical thinking, and practical application of math in real-life scenarios. With a focus on developing both computational skills and conceptual understanding, the book encourages active learning through examples, visual aids, and practice tasks tailored to the learning pace of pupils at this level.